A generalised optimal linear quadratic tracker with universal applications – part 1: continuous-time systems. Issue 2 (25th January 2017) - Ebrahimzadeh, Faezeh; Tsai, Jason Sheng-Hong; Liao, Ying Ting; Chung, Min-Ching; Guo, Shu-Mei; Shieh, Leang-San; Wang, Li
ABSTRACT: This paper presents a generalised optimal linear quadratic analog tracker (LQAT) with universal applications for the continuous-time (CT) systems. This includes: (1) a generalised optimal LQAT design for the system with the pre-specified trajectories of the output and the control input and additionally with both the input-to-output direct-feedthrough term and known/estimated system disturbances or extra input/output signals; (2) a new optimal filter-shaped proportional plus integral state-feedback LQAT design for non-square non-minimum phase CT systems to achieve a minimum phase-like tracking performance; (3) a new approach for computing the control zeros of the given non-square CT system; and (4) a one-learning-epoch input-constrained iterative learning LQAT design for the repetitive CT system.